Temperature-dependent leak tightness of elastomer seals after partial and rapid release of compression. (December 2015) - Grelle, Tobias; Wolff, Dietmar; Jaunich, Matthias
Abstract: A device has been designed, built and tested that allows the investigation of effects of dynamic loads on the leak tightness of elastomer seals at low temperatures. With the test setup, the compression of the tested seal can be reduced by a defined degree in a time period of less than 1 s. For the evaluation of the leak tightness, leakage rates can be determined. It was shown that the rapid partial release of an elastomer seal leads to its failure already at the beginning of the rubber–glass transition and, therefore, at significantly higher temperatures than the loss of leak tightness observed under static conditions.